Simulating the distribution of beached litter on the northwest coast of Scotland - Allison, Nicole L.; Dale, Andrew; Turrell, William R.; Aleynik, Dmitry; Narayanaswamy, Bhavani E. (Frontiers in Environmental Science, 2022)
Various field methods have been used globally in an attempt to understand and quantify plastic pollution. However, in regions, such as the west coast of Scotland, sparse populations, combined with complex coastlines of numerous islands, sea lochs and headlands, has resulted in limited field data. The Clyde Sea is the most populated and industrialised region on the west coast of Scotland and therefore a potential source of land-based plastic litter to the less populated coast to the north. This study first presents an analysis of Marine Conservation Society (MCS) citizen-science beach-clean data, from 1994 to 2019, revealing spatial patterns between beach-clean sites. Plastic litter was categorised into land, marine and unknown sources, with the most common items in these three categories being crisp packets, fishing rope and fragments, respectively. On the west coast of Scotland there is on average 380.3 ± 419.9 plastic items per 100 m of coast, with the site average number of items recovered ranging from 1-2355 per 100 m of coast. To simulate marine plastic litter movement from the Clyde Sea to a defined northwest model sub-area, an unstructured-grid hydrodynamic model was coupled with a particle tracking model subject to currents, diffusion, and wind. Three coastal boundary conditions were used to compare transport paths with or without particle beach resuspension, and for the resuspending cases, with or without a distinction between coastal type (retentive beaches versus reflective rocky coasts). Of the total released particles, the percentage that beached within the model sub-area, after a one-year model run, ranged between 45.7% - 88.3% depending on the coastal boundary condition. The Clyde Sea was found to be a potential source of beached land-based plastic litter to the north, as on average, 6.8% (range: 2.9% - 11.7%) of particles exited the Clyde Sea, crossed a defined northern boundary, and beached on the northwest coast. Both hydrodynamic and particle tracking models were tested, and the varying boundary conditions were compared to investigate holistic methodologies to better understand plastic pollution.